“Bull in the Boat” – A New Interpretation for One of the Depictions of Mithraic Iconography - Simon, Attila (Sapiens ubique civis, 2023)
For more than a century, the history of Mithras mysteries has been a his topic in religious history research. Countless works have been written on this subject since Franz Cumont. Numerous monographs have also been written on the subject of Mithras iconography, but there are elements that have not really come into the studies. Most of these works deal with the motif of tauroctony, the astronomical significance of which has been authentically proven by several excellent researchers. Among the iconographic elements that have survived in fewer numbers, there are several for which no acceptable interpretation has been found so far. One of these is the depiction of a bull in a moon-shaped boat, which occurred mainly in the Danube regions. In my presentation, I undertake to demonstrate the prevalence of this motif in the field of Mithraic representations and to try to give a new interpretation to this iconographic element that has so far been little studied.